2018
DOI: 10.7251/bii1801046m
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the patency loss of arteriovenous fistula for hemodialysis

Abstract: Uvod. Cilj rada je da se ispita učestalost ranih i kasnih postoperativnih komplikacijaarteriovenske fistule (AVF) i utvrde faktori povezani sa gubitkomprohodnosti AVF.Metode. Ispitivanje je obuhvatilo 250 bolesnika kojima je kreirana nativnapodlaktična AVF za hemodijalizu, a potom su praćeni najmanje šest mjeseci.Bolesnici su podijeljeni u dvije grupe: grupa 1, 50 bolesnika (30 muškaraca,65,9 ± 11,9 godina) kod koje je došlo do gubitka prohodnosti AVF poslije31,8 ± 38,8 mjeseci; grupa 2, 200 bolesnika (106 muš… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Of great importance for the occurrence of complications of AVF is the way of their use, and especially it is necessary to avoid premature puncture of AVF after surgery, repeated punctures in the same place, excessive compression. Examining the factors associated with the loss of AVF patency, we have previously shown that hypotension, diabetes, anemia, previous venous cannulation used for AVF, artery and vein quality, use of AVF for hemodialysis less than 45 days after its creation, number of intraoperative and postoperative complications, are significant independent risk factors for loss of AVF patency [16]. In addition to all these factors, we and many other authors emphasize the impor-tance of surgical technique and only strict adherence to all recommended details of AVF surgery can ensure the optimal result of the procedure [6,7,16,38−40].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of great importance for the occurrence of complications of AVF is the way of their use, and especially it is necessary to avoid premature puncture of AVF after surgery, repeated punctures in the same place, excessive compression. Examining the factors associated with the loss of AVF patency, we have previously shown that hypotension, diabetes, anemia, previous venous cannulation used for AVF, artery and vein quality, use of AVF for hemodialysis less than 45 days after its creation, number of intraoperative and postoperative complications, are significant independent risk factors for loss of AVF patency [16]. In addition to all these factors, we and many other authors emphasize the impor-tance of surgical technique and only strict adherence to all recommended details of AVF surgery can ensure the optimal result of the procedure [6,7,16,38−40].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Differences in the frequency of each complication can be explained by differences in surgical technique, AVF localization, diagnostic methods, but, above all, differences in the characteristics of patients and the quality of their blood vessels. It has been described that the age of patients, sex, underlying disease, comorbidities, but also the use and care of AVF significantly affect the occurrence of complications and survival of AVF [4,8,16].…”
Section: Introductionmentioning
confidence: 99%